Analysis of Emotions Using Electrooculography and Pupillary - Dr. C. Malathy, Ahana Chattopadhyay (International Journal of Advanced Science and Technology, 2020)
Today’s demand for systems with Human Centered computing grows, systems of automated tools with human gesture and emotion recognition capabilities are the need of the hour. Emotion Analysis and recognition has become an interesting topic of research among the computer vision research community. The  model proposed aims to analyze the emotions to give a clear a picture which gives a better emotion recognition and accuracies by EOG and Pupillary Reflex. The eyes are the important part of human beings and are very common in capturing emotions so the techniques used here is Electrooculography (EOG) which is actually captures the eye movements considering the face and forehead as a whole and another technique is Pupillary Reflex of eyes which gives the contraction and retraction of the pupil of the eyes which helps in describing emotions. The model will give the accuracy of capturing emotions and classifying it accordingly.